COLD AND HOT SMOKED NILE TILAPIA FILLETS: QUALITY AND YIELD OF PIGMENTED AND UNPIGMENTED FILLETS - Souza, M. L. R.; Viegas, E. M. M.; Kronka, S. N. [UNESP]; Amaral, L. A. [UNESP]; Parisi, G.; Coradini, M. F.; Goes, E. S. R. (Codon Publications, 2020)
Aiming evaluate the effects of smoking techniques on the quality of tilapia fillets, a 2x2 factorial scheme experiment was conducted comprising two smoking techniques (hot and cold) and two pigmentation (with and without). Cold smoked fillets and fillets with pigmentation demonstrated a greater yield. Hot smoked fillets were tenderer and presented lower moisture and greater ash and protein contents. The pigmentation did not influence the smoked fillet composition, but ash content was greater in fillets without pigmentation. The sensory acceptance of hot smoked fillets was better. The pigmentation influenced the color and appearance; however, fillets without pigmentation gave better flavor.
Keywords: benzo(a)pyrene; chemical composition; Oreochromis niloticus; organoleptic aspects; smoked yield